Muscular strength, flexibility and balance analysis in women practicing ballet pilates (Research, Society and Development, 2022)
Introduction: Ballet Pilates is a way of associating Pilates principles with Classic Ballet movements. The exercises employ body weight as a load, they can be adapted according to physical condition of each one. In a short time of practice, it is possible to observe the results, such as reducing weight, increasing muscle strength and improving posture. Objective: Analyze the muscular strength, flexibility and balance of women who practice Ballet Pilates, comparing them as variables before and after two months of practicing the sport. Methodology: The present study is of intervention and field, of comparative character and quantitative nature. A survey included 14 volunteers practicing the sport, aged 20 to 50 years old, and a data collection was carry out at the Tiradentes University. Data were collect using the Lafayette isometric dynamometer, the Sanny analog fleximeter and the Arkipelago baropodometry platform. Results: According to a strength analysis, muscle gains were observe, especially in the quadriceps, gluteus and calves, with statistical statistics for right quadriceps (p = 0.008) and left gluteus (p = 0.021). In the flexibility variable, differences were observed before and after the activity execution, with positive impact on the following muscle groups: torso (p = 0.004), hip flexors (p